Design and analysis of transmit/receive switch in triple-well CMOS for MIMO wireless systems - Poh, Andrew Hoe Suan (2009)
This paper presents the design and analysis of an RF transmit/receive switch in CMOS for multiple-input multiple-output (MIMO) wireless systems. First, both full-range and abridged quad-pole quad-throw (4P4T) switch architectures for MIMO systems with four antenna elements are comparatively studied. The full-range 4P4T switch is selected for circuit implementation because of its more switching states and lower insertion loss. The series connection and body-floating techniques are then employed in the circuit design to achieve an acceptable performance. Fabricated in 0.12-µm triple-well CMOS with an effective die area 0.35 X 0.19 mm2, the 4P4T switch exhibits less than 2.7-dB insertion loss and higher than 20-dB isolation over the frequency range from 2 to 10 GHz. It also attains measured power-handling capability more than 25 dBm at 2.4 and 5.8 GHz.